De Novo Food Allergy in Pediatric Recipients of Liver Transplant. Issue 2 (28th February 2022) - Mori, Francesca; Giovannini, Mattia; Barni, Simona; Trapani, Sandra; Indolfi, Giuseppe
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Allergic and atopic conditions, including food allergy, asthma, eczema and eosinophilic disease of the gastrointestinal tract after liver transplant in previously non-allergic children have been increasingly described. After a liver transplant, children can present mild to severe reactions to food allergens (ie, from urticaria-angioedema to life-threatening anaphylactic reactions). De novo post-transplant food allergy may become clinically evident in children who undergo liver transplant between a few months and a few years of transplant. The present narrative review aims to describe the spectrum of de novo post-transplant food allergy development, the current theories of pathogenesis, risk factors and to suggest possible clinical management strategies.